1974
DOI: 10.1111/j.1464-410x.1974.tb10163.x
|View full text |Cite
|
Sign up to set email alerts
|

A Classification and Quantitative Histological Study of Abnormal Ureters in Children

Abstract: Summary A gross and quantitative study of the muscle and connective tissue and elastic tissue has been carried out on a series of 78 abnormal ureters in children. The ureters have been classified into 5 classes: (A) normal; (B) ureters with irregular dilatations; (C) slightly dilated ureters with muscular hypertrophy and hyperplasia; (D) elongated and dilated ureters with muscular hypertrophy and hyperplasia but probably decompensated; (E) grossly distended and elongated ureters having an increase in elastic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Despite some reports to the contrary [Gabella, 1975;Cortivo et al, 19811, the bulk of the available literature indicates that collagen becomes abundant in obstructed viscera, including urinary tract organs [Brent, 1973;Emery and Gill, 1974;Brent and Stephens, 19751 and the pregnant or artificially distended rat uterus [Harkness and Harkness, 1956;deMattos et al, 1967;Cullen and Harkness, 1968;Gunga-Smith and Woessner, 19851. In the present study, collagen deposits were observed not only between individual muscle cells but also, much more abundantly, in the interstitial tissue between muscle fascicles. This, however, should be viewed with caution and must be verified morphometrically in view of the previously reported data on collagen content and concentration of the detrusor in the same rabbit model [Malkowicz et al, 19861.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some reports to the contrary [Gabella, 1975;Cortivo et al, 19811, the bulk of the available literature indicates that collagen becomes abundant in obstructed viscera, including urinary tract organs [Brent, 1973;Emery and Gill, 1974;Brent and Stephens, 19751 and the pregnant or artificially distended rat uterus [Harkness and Harkness, 1956;deMattos et al, 1967;Cullen and Harkness, 1968;Gunga-Smith and Woessner, 19851. In the present study, collagen deposits were observed not only between individual muscle cells but also, much more abundantly, in the interstitial tissue between muscle fascicles. This, however, should be viewed with caution and must be verified morphometrically in view of the previously reported data on collagen content and concentration of the detrusor in the same rabbit model [Malkowicz et al, 19861.…”
Section: Discussionmentioning
confidence: 99%
“…Elastin deposits were constantly observed in the partially obstructed rabbit detrusor in the present study; these deposits were mainly in the form of intercellular microfibrils and interstitial fibers with amorphous cores (that became intensely electron-dense by orcein staining) between muscle fascicles. Elastin has been reported to be increased in the obstructed human bladder [Cortivo et al, 19811, the obstructed human and rabbit ureter [Emery and Gill, 1974;Gee and Kiviat, 19751, and the pregnant uterus [Downie, 1972;Downie et al, 1973;Gunga-Smith and Woessner, 19851. Abatangelo et al, [ 19771, however, reported no change in the elastin content of the dilated human ureter in comparison to control material, as determined biochemically and expressed in terms of dry weight of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…
Dilatation of the adult ureter is generally due to an obstruction of its terminal segment or, less frequently, of the lower urinary tract. This dilatation is usually accompanied by tortuosity and thickening of the ureteric wall.It is also generally accepted that the "congenital" megaloureter may be due to a not wellidentified ureteral form of obstruction.In children it has been demonstrated (Emery and Gill, 1974), by histological techniques, that the tortuous and dilated ureters show an increase in connective tissue components and muscle, even though, from these observations it was not possible to estimate the amount of the elastic tissue. Pagano et al (1976), using chemical and histochemical procedures, showed unequivocally that the elastic tissue increases significantly in the dilated ureters in children.In this case the increase of the elastin was interpreted as a reactive response of the ureteric wall to the increased hydrostatic pressure.In the adult ureter it has been shown by Stein and Weinberg (1962) that there is an increase of the muscle and fibrous tissue, while the elastic tissue seems to remain constant.No quantitative estimation, however, has been done in order to establish the exact amount of the elastic tissue and its chemical composition.
…”
mentioning
confidence: 96%
“…In children it has been demonstrated (Emery and Gill, 1974), by histological techniques, that the tortuous and dilated ureters show an increase in connective tissue components and muscle, even though, from these observations it was not possible to estimate the amount of the elastic tissue. Pagano et al (1976), using chemical and histochemical procedures, showed unequivocally that the elastic tissue increases significantly in the dilated ureters in children.…”
mentioning
confidence: 96%
“…Previous studies on obstructed bladders [1,3,8,9] and on dilated ureters in children [2,14] have demonstrated that there is a measurable elastin increase during bladder obstruction [1,8,9,11]. It has been proposed that this increase in elastin compensates for the raised intraluminal pressure [1].…”
mentioning
confidence: 99%